Antifungal Efficacy Of Essential Oils Against Fusarium Oxysporum F. Sp. Lycopersici (Journal of Plant Disease Sciences, 2020)
`Five essential oils were evaluated against Fusarium oxysporum f.sp. lycopersici to check their antifungal activity. The most active essential oils were lemongrass, peppermint, clove, Thyme and lavender. The anti fungal activity of these essential oils were tested with different concentrations of 0.5%, 1%, 1.5%. Amongst, Clove oil inhibition was high as against control.The effect of essential oils on mycelia growth was significantly affected the growth of the pathogen. However, clove oil (47.21%) and lavender oil,(32.08%) found best to restrict the mycelia growth of the pathogen. Clove oil and lemongrass were little closed in restricting the growth of the pathogen.
Keywords: Fusarium oxysporum f.sp lycopersici; Essential oils; Antifungal Activity